Snap and split: an android application for bill payment using tesseract OCR - kata, Sugamya; Pabboju, Suresh; Babu, Vinaya; Medishetti, Anudeep (International Journal of Engineering & Technology, 2018)
Snap and split is a mobile application which uses Optical character recognition to recognize the bill from a printed sheet. It provides an option to tag users and telling them about the shared bill by pushing a notification. Users can tap and pay the bills instantly.Tesseract is one of the best image recognition tools present and uses separate packs for various languages.Â Â Â